Frequency of Ectopic Pregnancy and its Management at Ayub Teaching Hospital Abbottabad - Fareed, Sumaira; Khan, Atyya Bibi; Bibi, Iqra; Nasir, Menahil (Indus Journal of Bioscience Research, 2025)
Background: Ectopic pregnancy is a life-threatening condition in which a fertilized ovum implants outside the uterine cavity, most commonly in the fallopian tube. It contributes significantly to maternal morbidity and mortality during the first trimester, particularly in low-resource settings where delayed diagnosis limits conservative treatment options. Objective: To determine the frequency and management patterns of ectopic pregnancy among women presenting to Ayub Teaching Hospital, Abbottabad. Study Design: Cross-sectional study. Duration and Place of Study: This study was conducted over six months, from July 2024 to December 2024, in the Department of Obstetrics and Gynecology, Ayub Teaching Hospital, Abbottabad. Methodology: A total of 67 women aged 18–40 years with suspected ectopic pregnancy were evaluated through clinical examination, serum β-hCG, and ultrasound. Patients with renal disease or bleeding disorders were excluded. Demographic and clinical variables were recorded, and management approaches were categorized as medical (methotrexate) or surgical (laparoscopic/laparotomy). Results: The mean age of participants was 28.88 ± 6.54 years, with a mean BMI of 27.49 ± 4.37 kg/m². The frequency of ectopic pregnancy was 10.4% (7 cases). Among these, surgical management was performed in 6 patients (85.7%), while only 1 case (14.3%) was treated medically. Diabetes showed a significant association with ectopic pregnancy (p